Surviving Warfare Adversities. A Brief Survival Advice for Civilians Under War Stress - Shalev, Arieh Y (Psychosomatic Medicine and General Practice, 2022)
As the Ukrainian war rages, countless civilians are exposed to shelling, bombardments, relocation, loss of live and other modalities of war-related adversities. Whilst much has been learned about the late psychological outcome of traumatic exposure, , for most civilians the task at hand now is to successfully survive whatever level of adversity and horror they have been exposed to; efficiently protect themselves and others around them, and ultimately emerge victorious and minimally scathed by war. This document offers an easy-to-follow survival advice. We start by defining war stress and its many facets, review successful and less successful ways to mitigate war stress, outline critical aspects of life that must be dealt with during war, and provide a simple self-assessment tool of one’s achievement and resilience.